2013
DOI: 10.1155/2013/234031
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Changes in Thyroid Related Hormones among Pregnant Women Residing in an Iodine Deficient Urban Area

Abstract: Problem Statement. Thyroid gland in women undergoes functional changes during pregnancy. A few studies have described such changes in pregnant women residing in iodine deficient areas. Objective. To document these changes in pregnant women residing in Lahore, a low iodine intake urban area of Pakistan. Patients and Methods. In 254 pregnant women, data of FT4, FT3, and TSH during the first and subsequent trimesters were obtained and compared with those of 110 nonpregnant women. These hormones were determined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
(50 reference statements)
1
15
0
Order By: Relevance
“…European pregnant women in many countries, including Belgium 11 , the Czech Republic 12 , Spain 13 , 14 , the United Kingdom 15 17 , Denmark 18 , Norway 19 , and France 20 , 21 , and those in the United States 20 , 22 , Australia 23 and New Zealand 24 have been documented well inadequate iodine intake. Nearly 80% of pregnant women in Vietnam 25 , 70% in Philippine 26 and more than half in Pakistan 27 had low UIC, while in Africa 28 , 29 and in south America 30 , pregnant women have already recorded iodine deficiency. Our findings confirm this information and further emphasize the need to surveillance pregnant women in intervals, even after the goal of elimination of IDD have achieved.…”
Section: Discussionmentioning
confidence: 99%
“…European pregnant women in many countries, including Belgium 11 , the Czech Republic 12 , Spain 13 , 14 , the United Kingdom 15 17 , Denmark 18 , Norway 19 , and France 20 , 21 , and those in the United States 20 , 22 , Australia 23 and New Zealand 24 have been documented well inadequate iodine intake. Nearly 80% of pregnant women in Vietnam 25 , 70% in Philippine 26 and more than half in Pakistan 27 had low UIC, while in Africa 28 , 29 and in south America 30 , pregnant women have already recorded iodine deficiency. Our findings confirm this information and further emphasize the need to surveillance pregnant women in intervals, even after the goal of elimination of IDD have achieved.…”
Section: Discussionmentioning
confidence: 99%
“…It has to produce adequate amounts of thyroid hormone in order to meet the demands of the mother and the fetus, as up till the 12th week of gestation, the fetus is completely dependent on the mother for its supply of thyroid hormones [1]. The fetal thyroid gland begins to produce thyroid hormones by the end of the first trimester but that too, not independently, as it still is in need of an adequate supply of iodine from the mother [2]. In order to meet this increased demand, the thyroid gland undergoes several structural and functional changes, induced by the several physiological mechanisms in the mother’s body explained ahead.…”
Section: Introductionmentioning
confidence: 99%
“…According to few authors, differences in free thyroid hormone levels during pregnancy can also occur due to flaws or variations in the method employed to determine the hormone levels [4,9]. A local study conducted by Elahi et al on pregnant women in Lahore showed FT4 levels decreased during the first trimester of pregnancy whereas TSH and FT3 values increased [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…documented the prevalence of iodine deficiency, goiter and thyroid disorders in pregnant females in Lahore, Pakistan. [ 3 4 5 ] Palpable goiter prevalence as high as 12% and 23% has been reported in India in adults[ 6 ] and children,[ 7 ] respectively. There is, however, no data available for prevalence of thyroid disorders in the general population living in nonmountainous regions of Pakistan.…”
Section: Introductionmentioning
confidence: 99%